2017
DOI: 10.1097/ta.0000000000001471
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in brain-derived neurotrophic factor and insulin-like growth factor-1 protein levels after penetrating ballistic-like brain injury in rats

Abstract: Our findings demonstrate that PBBI results in a brief upregulation of BDNF and IGF-1 during early posttraumatic period, providing critical information for interventions aiming to enhance neuronal survival and brain plasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…MiR-335 targets insulin-like growth factor receptor (IGF-R) (Gong et al, 2014). The IGF-1/IGF-R pathway is crucial to cellular metabolism affected by TBI and the ligand, IGF-1, is increased in damaged cortical and hippocampal regions 3-7 day after PBBI (Madathil and Saatman, 2015;Madathil et al, 2017). It is possible that this observation is relevant to neurogenesis during attempted repair (Madathil et al, 2013).…”
Section: Pbbi Leads To Temporally Specific Mirna Dysregulation Associmentioning
confidence: 99%
“…MiR-335 targets insulin-like growth factor receptor (IGF-R) (Gong et al, 2014). The IGF-1/IGF-R pathway is crucial to cellular metabolism affected by TBI and the ligand, IGF-1, is increased in damaged cortical and hippocampal regions 3-7 day after PBBI (Madathil and Saatman, 2015;Madathil et al, 2017). It is possible that this observation is relevant to neurogenesis during attempted repair (Madathil et al, 2013).…”
Section: Pbbi Leads To Temporally Specific Mirna Dysregulation Associmentioning
confidence: 99%
“…Most studies of TBI in juvenile rats have found greater BDNF protein concentration and BDNF mRNA expression up to 7 days after injury relative to sham or control animals [40][41][42]. In adult models, rats with TBI had higher BDNF expression acutely (within 6 h of injury) compared to shams, suggesting an upregulation of BDNF in the acute period, but similar or even lower BDNF expression compared to the sham group chronically after injury [43][44][45][46][47]. BDNF expression in adult models of ABI is associated with recovery in many of these studies [46,48,49].…”
Section: Bdnf In Preclinical Models Of Pediatric Abimentioning
confidence: 99%
“…The ability to predict mortality and injury severity may facilitate the development of clinical guidelines for managing pTBI. 15 Several biomarkers are reported to be altered after PBBI, including GFAP (glial fibrillary acidic protein; astrogliosis/astroglial injury), [16][17][18] brain-derived neurotrophic factor (BDNF; neurogenesis/neuroprotection), 19 ubiquitin C-terminal hydrolase-L1 (UCH-L1; neuronal cell body injury), 20 cathepsin B (CatB; apoptosis/ cell necrosis), 21 and microRNA (miRNA; astrogliosis/ inflammation/neurodegeneration). 22,23 Considering that pTBI and polytrauma often occur concurrently in the setting of emergency medicine, we hypothesized that the use of brain-specific and global injury biomarkers can reliably identify HX+HS and frontal PBBI with and without systemic insults (HX+HS) to diagnose and differentiate combined injury from isolated pTBI.…”
Section: Introductionmentioning
confidence: 99%
“…Several biomarkers are reported to be altered after PBBI, including GFAP (glial fibrillary acidic protein; astrogliosis/astroglial injury), 16–18 brain-derived neurotrophic factor (BDNF; neurogenesis/neuroprotection), 19 ubiquitin C-terminal hydrolase-L1 (UCH-L1; neuronal cell body injury), 20 cathepsin B (CatB; apoptosis/cell necrosis), 21 and microRNA (miRNA; astrogliosis/inflammation/neurodegeneration). 22 , 23 …”
Section: Introductionmentioning
confidence: 99%